“I didn’t see a sheep”: perspectives of lecturers and students at veterinary schools in Great Britain on learning about lameness in sheep - Clifton, Rachel; Bamford, Kate; Green, Laura (Frontiers in Veterinary Science, 2023)
Introduction Great Britain has over 15 million ewes. Lameness is one of the top three most economically important diseases for the sheep industry, costing about £80 million per annum. The prevalence of lameness reduced from 10% to 5% between 2004 and 2013 but further reduction is unlikely because many farmers and agricultural students still believe in, and use, ineffective practices to control lameness. Unfortunately, many veterinary practitioners consider themselves insufficiently knowledgeable to work confidently with sheep farmers, and many sheep farmers agree with them. Another route to improve control of lameness is to ensure that all new veterinary graduates are competent to advise farmers. Methods Our study investigated how veterinary students are taught about management of lameness in sheep. Ten lecturers from eight veterinary schools were interviewed, and 33 students from four veterinary schools participated in four focus groups; all were recorded, transcribed, and analysed using directed qualitative content analysis. Results Teaching time and opportunities for students to gain clinical experience of lameness were very limited. Students were not confident they could diagnose causes of lameness and listed many practices, including ineffective ones, to manage footrot. Discussion We conclude that GB veterinary students are graduating without evidence-based understanding and clinical experience necessary to advise farmers on management of lameness in sheep. Given the importance of lameness in sheep in GB we conclude that an alternative approach to education on lameness in sheep could help to ensure that new graduate veterinarians can contribute to control of lameness in sheep.